Pelatihan Layanan Konseling Terhadap Problem Belajar Siswa Di Sekolah Dasar - Ratno Susanto; Lubis, Siti Khodijah; Pangestu, Deviyanti; Afandi, Ahmad (Universitas Nusantara PGRI Kediri, 2025)
Learning problems are one of the main challenges often faced by students at the elementary school level. Various factors, both internal and external, can affect students' ability to understand and absorb learning materials. Unfortunately, many elementary schools do not yet have professional counselors to handle this problem. This community service activity aims to provide basic counseling service training to elementary school teachers so that they are able to identify and handle student learning problems effectively. The training was carried out through interactive lecture methods, group discussions, case simulations, and further assistance. The evaluation results showed an increase in participants' understanding from an average pre-test score of 58 to 84 on the post-test. In addition, teachers began to apply a counseling approach in dealing with students with problems more empathetically. Although there were several obstacles in the implementation in the field, this training has proven to have a positive impact and is relevant to be implemented sustainably in an effort to improve the quality of elementary education services.